(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article describes prospective-teacher students’ reversible thinking in solving problems. The problem was focused on mathematical insurance. This qualitative research involves prospective-teacher students with high math competence in major of mathematics education who had passed mathematical insurance course. The data was collected by providing two reversible problems and then having an interview. Those two problems were reversible. The first involved inverse, while the second not. The data was analyzed by referring to the procedure problem solving by Polya and the aspects of reversible thinking such as inversion and reciprocity. The result found that the students were not capable to solve either inverse or reciprocal problems. Otherwise, they could only solve problems that had no relation to inverse. Thus, students’ reversible thinking in solving mathematical insurance problems was found in trouble.